Investigating fibrinogen levels as a biomarker for immune inflammation severity in COPD patients across GOLD stages - Hamidullah,; Sajjad Ali,; Ashraf,; Imranullah,; Ishtiaq Ahmad, (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the association between fibrinogen levels and immune inflammation severity in patients with chronic obstructive pulmonary disease at different stages of the Global Initiative for Chronic Obstructive Lung Disease classification. Method: The descriptive, prospective, cross-sectional study was conducted from January 2022 to November 2023 at the Pulmonology Department, Mardan Medical Complex, Khyber Pakhtunkhwa, Pakistan, and comprised chronic obstructive pulmonary disease patients of either gender aged 40-85 years. Fibrinogen levels and systemic immune-inflammatory markers were measured, and disease severity was classified based on the Global Initiative for Chronic Obstructive Lung Disease classification. Independent predictors of fibrinogen levels as well as the diagnostic accuracy of biomarkers for predicting advanced chronic obstructive pulmonary disease were identified. Data was analysed using SPSS 26. Results: Of the 253 patients, 147(58.10%) were males and 106(41.89%) were females. Most of the patients were aged 40-50 years 72(28.45%), followed by 50-60 years 57(22.52%). A strong positive correlation was observed between fibrinogen levels and chronic obstructive pulmonary disease severity (r=0.815, p<0.001). The diagnostic accuracy of fibrinogen for predicting advanced disease stages was reliable, having an area under the curve of 0.910. Conclusion: Fibrinogen levels could be used as a marker for immune inflammation severity in chronic obstructive pulmonary disease patients.